Biallelic mutation of human SLC6A6 encoding the taurine transporter TAUT is linked to early retinal degeneration. Issue 10 (25th July 2019) - Preising, Markus N.; Görg, Boris; Friedburg, Christoph; Qvartskhava, Natalia; Budde, Birgit S.; Bonus, Michele; Toliat, Mohammad R.; Pfleger, Christopher; Altmüller, Janine; Herebian, Diran; Beyer, Mila; Zöllner, Helge J.; et al.
ABSTRACT: We previously reported that inactivation of the transmembrane taurine transporter (TauT or solute carrier 6a6) causes early retinal degeneration in mice. Compatible with taurine's indispensability for cell volume homeostasis, protein stabilization, cytoprotection, antioxidation, and immuno‐ and neuromodulation, mice develop multisystemic dysfunctions (hearing loss; liver fibrosis; and behavioral, heart, and skeletal muscle abnormalities) later on. Here, by genetic, cell biologic, in vivo 1 H–magnetic resonance spectroscopy and molecular dynamics simulation studies, we conducted in‐depth characterization of a novel disorder: human TAUT deficiency. Loss of TAUT function due to a homozygous missense mutation caused panretinal degeneration in 2 brothers. TAUTp.A78E still localized in the plasma membrane but is predicted to impact structural stabilization. 3 H‐taurine uptake by peripheral blood mononuclear cells was reduced by 95%, and taurine levels were severely reduced in plasma, skeletal muscle, and brain. Extraocular dysfunctions were not yet detected, but significantly increased urinary excretion of 8‐oxo‐7, 8‐dihydroguanosine indicated generally enhanced (yet clinically unapparent) oxidative stress and RNA oxidation, warranting continuous broad surveillance.—Preising, M. N., Görg, B., Friedburg, C., Qvartskhava, N., Budde, B. S., Bonus, M., Toliat, M. R., Pfleger, C., Altmüller, J., Herebian, D., Beyer, M., Zöllner, H. J., Wittsack, H.‐J., Schaper, J., Klee, D., Zechner, U., Nürnberg, P., Schipper, J., Schnitzler, A., Gohlke, H., Lorenz, B., Häussinger, D., Bolz, H. J. Biallelic mutation of human SLC6A6 encoding the taurine transporter TAUT is linked to early retinal degeneration. FASEB J. 33, 11507–11527 (2019). www.fasebj.org